Health related fitness of adolescents participating in a sports program - NOGUEIRA, Julia Aparecida Devide; PEREIRA, Cleilton Holanda (Brazilian journal of physical education and sport, 2014)
The present study aims to analyze AFRS of adolescent participating in the Olympic Villages (VO) in Fortaleza, Ceará according to sex, age and permanence in the program. This is an analytical cross-sectional study with random representative sample of 344 adolescents of both sexes, aged between 11 and 16 years. Body weight and height were measured to calculate BMI. To evaluate AFRS, flexibility, muscular strength/endurance (FRM) and cardiorespiratory fitness (ApC) were measured using the Esporte Brasil (PROESP-BR) protocol. For data analysis, descriptive statistics, Student's t test, one-way ANOVA and binary logistic regression were used. Of the participants, 15.1% did not meet the minimum criteria for BMI; 28.2% for flexibility, 32.6% for FRM and 45.6% for ApC, with significant influence of sex and age. Boys were more difficult to meet the criteria for flexibility (χ2 = 5.96, p < 0.01) and FRM (χ2 = 12.33, p < 0.001), and the older group showed greater difficulty in meeting the criteria for FRM (χ2 = 5.74, p < 0.05). Teens who participate longest at the VO tend to be, more likely to achieve desired levels for flexibility (not significantly) (OR = 1.23, 95%CI: 0.65-2.33) and ApC (RC = 1.35, 95%: 0.77-2.36) and fewer chances for BMI (OR = 0.43, 95%CI: 0.17-1.08) than those involved more recently. Adolescent participants in VO have a high prevalence of physical low fitness, especially ApC, with significant influence of sex and age, but unrelated to the permanence in the program. These results indicate the need for reflection, especially by physical education professionals, about the strategies adopted in the sports projects to effectively promote improvements in AFRS of the population.